The Tyranny of the Tenths. The Rise and Gradual Fall of Forward Guidance in Sweden 2007-2018 - Fredrik N. G. Andersson; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2019)
This paper examines the Swedish experience of forward guidance 2007-2018. We focus on three interrelated issues: first, the effects of forward guidance on the discussion within the Board of Directors of the Riksbank, second, on the communication between the Riksbank and the public, and third, on the interest rate expectations held by various groups in Swedish society. We conclude that forward guidance has had negative effects on the dialogue within the Board as well on the communication between the Riksbank and the public. In addition, forward guidance has failed to affect expectations about interest rates in a systematic and significant way. We trace the roots of these consequences to the inability of the Riksbank to forecast its future policy rate three years ahead with any reasonable accuracy. The Riksbank has learned from this dismal performance and partially abandoned forward guidance, returning to a focus on the rate of inflation – as it did prior to the introduction of forward guidance.
Keywords: E40; E43; E47; E50; E52; E65; 330; forward guidance; central bank communication; interest rate forecasting; inflation targeting; the Riksbank; monetary policy; Sweden